TEGDMA releasing in resin composites with different filler contents and its correlation with mitochondrial mediated cytotoxicity in human gingival fibroblasts. Issue 6 (5th March 2019) - Liu, Beilei; Gan, Xueqi; Zhao, Yuwei; Chen, Junsheng; Yu, Hongdou; Gao, Jing; Yu, Haiyang
Abstract: Compositions of resin composite exhibit cytotoxicity, especially Triethylene‐glycol‐dimethacrylate (TEGDMA), yet the underlying mechanisms and its relationship with filler content are poorly understood. Here, specimens of five composites (VITA LC, VITA ZETA, Z350, Filtek P60, and AP‐X), containing different filler size and weight, were immersed into culture medium for 72 h. After TEGDMA quantification, the resin composite eluates were used to incubate HGFs. Cellular viability was evaluated. Total reactive oxygen species (ROS) and mitochondrial ROS were detected to assess oxidative stress. Adenosine triphosphate and cytochrome c oxidase (CcO) activity, mitochondrial membrane potential and morphology, mitochondrial biogenesis regulators were analyzed to evaluate mitochondrial functions. Results showed that TEGDMA release negatively correlated to filler size and weight of tested composites. Although cell viability reduction was not significant, total and mitochondrial ROS production showed a positive relationship with the amount of TEGDMA in composite eluates. Furthermore, the expression of mitochondrial biogenesis markers and mitochondrial fusion protein, were markedly elevated in TEGDMA rich eluates, especially in VITA‐LC group, shown as elongated mitochondrial morphology and aberrant mitochondrial functions. Overall, TEGDMA could elute easier from those resin composites with less filler content and cause oxidative stress in HGFs via mitochondria dysregulation. These data can be instructive to optimize the synthesis of resin composites from the perspective of biocompatibility. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1132–1142, 2019.